What were the impacts of the Committee on Safety of Medicines warning and publication of the NICE guidelines on trends in child and adolescent antidepressant prescribing in primary care? A population based study. Issue 8 (6th August 2019) - Tiffin, Paul A; Mediavilla, Jose L; Close, Helen; Kasim, Adetayo S; Welsh, Patrick; Paton, Lewis W; Mason, James M
Abstract : Objectives: To assess the impact of both the Committee on Safety of Medicines (CSM) warning (December 2003) and the National Institute for Health and Care Excellence (NICE) guidance (September 2005) on antidepressant prescription rates in children and adolescents within the UK primary care service. Setting: Population based study of primary care antidepressant prescribing using the Clinical Practice Research Datalink (CPRD). Participants: Under-18s presenting to primary care with a depressive disorder or related diagnostic code recorded in the CPRD. Primary outcome measure: Antidepressant prescription rates per month per 100 000 depressed 4–17 year olds. Results: Following the CSM warning, the prior trend towards increased prescribing rates for selective serotonin reuptake inhibitors (SSRIs) in children was significantly reversed (β for change in trend −12.34 (95% CI −18.67 to −6.00, p<0.001)). However, after the publication of the NICE guidelines the prior trend towards increased prescribing resumed for those SSRIs mentioned as potential treatments in the guidance (fluoxetine, citalopram and sertraline) (β for change in trend 11.52 (95% CI 5.32 to 17.73, p<0.001)). Prescribing of other SSRIs and tricyclics remained low. Conclusions: Despite a strong emphasis on psychosocial interventions for child and adolescent depression, it may be that the NICE guidelines inadvertently encouraged further antidepressant prescribing, at least for those SSRIs cited. Although the guidelines gave cautions and caveats for the use of antidepressants, practitioners may have interpreted these recommendations as endorsing their use in young people with depression and related conditions. However, more accurate prevalence trend estimates for depression in this age group, and information on the use of psychosocial interventions would be needed to rule out other reasons underlying this increase in prescribing.